2012
DOI: 10.5507/bp.2012.028
|View full text |Cite
|
Sign up to set email alerts
|

Glibenclamide-pregnenolone derivative has greater hypoglycemic effects and biodistribution than glibenclamide-OH in alloxan-rats

Abstract: Aim. The present study was designed to investigate the activity of two glibenclamide derivatives on glucose concentration. An additional aim was to identify the biodistribution of glibenclamide derivatives in different organs in a diabetic animal model. Methods. The effects of two glibenclamide derivatives on glucose concentration were evaluated in a diabetic animal model. In addition, glibenclamide derivatives were bound to Tc-99m using radioimmunoassay methods. To evaluate the pharmacokinetics of the glibenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
(24 reference statements)
1
13
0
Order By: Relevance
“…Thus, a study conducted in the general population is needed to evaluate the effect of progestogen on T2DM. Additionally, an experimental research with rats reported that the effect of a high dose of glibenclamidepregnenolone on anti-hyperglycemic activity was better than glibenclamide or glibenclamide-OH, which was in consistence with the present study to some degree (38). The results of gender stratification analysis were similar to the findings in all participants, which partly may be due to the similar source of progestogen production (adrenal) in postmenopausal women and men (39,40).…”
Section: Discussionsupporting
confidence: 88%
“…Thus, a study conducted in the general population is needed to evaluate the effect of progestogen on T2DM. Additionally, an experimental research with rats reported that the effect of a high dose of glibenclamidepregnenolone on anti-hyperglycemic activity was better than glibenclamide or glibenclamide-OH, which was in consistence with the present study to some degree (38). The results of gender stratification analysis were similar to the findings in all participants, which partly may be due to the similar source of progestogen production (adrenal) in postmenopausal women and men (39,40).…”
Section: Discussionsupporting
confidence: 88%
“…In a different anti-diabetic assay model, betulinic acid was found to increase glucose uptake and enhanced glycogen synthesis 14 . It is proposed that a steroid nucleus is important for a high hypoglycemic effect and possibly conditioning the high degree of lipophilicity 15 and they exhibit anti-diabetic properties with relatively low toxicity 16,17 . According to Li et al 18 , the mechanism of action of terpenoids and steroids in in-vivo studies might occur through stimulation of pancreatic islets leading to an increase in insulininduced glucose uptake.…”
Section: Resultsmentioning
confidence: 99%
“…Group II: n= 10, control Diabetic rats, received daily dose of distilled water. Group III: n= 10, diabetic rats treated with metformin at a dose 350 mg/kg bw/day (Figueroa-Valverde et al, 2012). Group IV: n= 10, diabetic rats treated with metformin at a dose 350 mg/kg bw/day (Figueroa-Valverde et al, 2012) and Nigella sativa oil at a dose 1 mL/kg bw/day (Zaoui et al, 2002).…”
Section: Experimental Designmentioning
confidence: 99%
“…Group III: n= 10, diabetic rats treated with metformin at a dose 350 mg/kg bw/day (Figueroa-Valverde et al, 2012). Group IV: n= 10, diabetic rats treated with metformin at a dose 350 mg/kg bw/day (Figueroa-Valverde et al, 2012) and Nigella sativa oil at a dose 1 mL/kg bw/day (Zaoui et al, 2002). Group V: n= 10, diabetic rats treated with Nigella sativa oil at a dose 1 mL/kg bw/day (Zaoui et al, 2002).…”
Section: Experimental Designmentioning
confidence: 99%